Patients' serum and urine as easily accessible samples for the measurement of non-vitamin K antagonist oral anticoagulants - Harenberg, Job; Weiß, Christel; Krämer, Roland; Wehling, Martin (Seminars in thrombosis and hemostasis, 2015)
Measurement of the anticoagulant effect of non-vitamin K antagonist oral anticoagulants (NOAC) may be desirable, in particular in patients with acute medical conditions. Useful methods should give results rapidly within minutes, should be easy to perform, specific, and sensitive. Using plasma samples, chromogenic assays can be made to be specific for the two types of NOAC (factor Xa and thrombin inhibitors), and also hemoclot and ecarin clotting time specific for dabigatran. If plasma samples anticoagulated with sodium citrate are not available, blood samples anticoagulated with ethylene diamine tetraacetic acid or serum samples may be regarded as alternatives for the determination of NOAC. At present, dabigatran cannot be determined from serum samples because it may be consumed during the clotting process to obtain serum. NOAC can be determined in urine samples due to their renal elimination. Quantitative methods are preferable to qualitative methods, although the latter may be advantageous in some situations, being developed as point-of-care tests for oral factor Xa and thrombin inhibitors. In these tests, the presence and absence of NOAC in urine can be identified with the naked eye after a few minutes and these tests are highly specific and sensitive. New assays such as a semiquantitative determination in urine samples and measurement using other sample matrices are currently under development.